Self-Control and Self-Boundaries of Boys' Love We are Series Fans on Social Media X as a Curative Effort to Overcome LGBTQ - Tauzia Harari; Irhamni Rahman (International Journal of Social Welfare and Family Law, 2026)
The popularity of the boys love (BL) genre, a key representation of the LGBTQ community, raises concerns about its potential negative impact on social pathology related to LGBTQ behaviors among fans. Despite the stigma labeling BL enthusiasts as exhibiting deviant sexual behavior (homosexuality), early observations and field findings show that most fans are heterosexual and do not exhibit such behavior. Instead, their engagement represents a cumulative effort to support LGBTQ representation. This research uses a qualitative case study approach, conducted on social media X over four months. Key findings suggest that the primary curative efforts by fans to address the social pathology of LGBTQ are self-control and the establishment of self-boundaries. Self-control is demonstrated through cognitive and decision-making control, while self-boundaries are seen in fans' understanding that fictional content should not be translated into heteronormative reality. Strengthening self-control and self-boundaries lays the foundation for further curative actions, preventing fans from becoming fully integrated into the LGBTQ community.